Baring Bearma’s Bounty. Human and animal signatures in the Quaternary contexts of the Bearma Valley, Central India - Yezad Pardiwalla; Vijay Sathe (Quaternary Environments and Humans)
The rich Palaeolithic and fossil records of the Narmada and Son Valleys dominate paleoanthropological research from Central India, in large part because of their well-preserved Quaternary deposits. While data from other river valleys is emerging, finding both lithics and fauna in close proximity remains rare and spatio-temporal inconsistencies make assessment of implications for the larger area challenging. Ongoing investigations along the Bearma, the largest tributary of the River Sonar, has yielded a low-density fossil assemblage across three localities and a proximally located Large Flake Acheulean (LFA) site. The small fossil assemblage currently consists of both cranial and post-cranial elements in differing states of completeness and preservation, likely a function of post-depositional impacts and the time elapsed since exposure. Many of the important large mammalian herbivore species belonging to bovid, equid, cervid and proboscidean taxa that are commonly found during the Late Quaternary of the Indian Subcontinent are represented, making the region worthy of comparison with neighbouring fossiliferous areas. The new Palaeolithic site encountered less than 500 m downstream from the fossil localities is almost exclusively LFA technology in nature made primarily on slabs of Vindhyan sandstone. Preliminary analysis of the collected artefacts indicates a focus on the production of large flake blanks and debitage products from large cores configured according to various unifacial and bifacial technological methods. The frequency of these elements suggests the use of the area as a factory site, while the unmistakable presence of bifaces and other tools warrant broader interpretations. With the current lack of stratigraphic and chronometric data on either assemblage, it is premature to draw any chrono-contextual associations between the fossils and artefacts. However, this ∼5 km stretch of the Bearma yielding two significant proxies presents an excellent opportunity to understand hominin behaviour during the Quaternary and fill both geographical and temporal gaps in Central India.